1996
DOI: 10.1111/j.1600-0773.1996.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rat and Human Liver Slices for the Detection of Steroid Hormone‐Induced DNA‐Adducts in vitro by Means of the 32P‐Postlabeling Technique

Abstract: Precision cut liver slices from humans and rats were used to investigate the covalent binding of xenobiotics to the DNA by means of the (32)P-postlabeling technique. Human liver slices were incubated with the structurally related steroid hormones chlormadinone acetate (5 mu g/ml), cyproterone acetate (0.01-5 mu g/ml), megestrol acetate (5 mu g/ml), and the positive control 2-aminofluorene (0.01-5 mu g/ml), which is known for its marked ability to form DNA-adducts in vivo. Rat liver slices were incubated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Because this drug is widely used in clinic, many studies have adressed its carcinogenic potential in human and most of the studies have come to the agreement that the liver cancer risk associated with the use of CPA is low, if it exists (Hinkel et al, 1996;Kasper, 2001;Kattan et al, 1994;Laron and Kauli, 2000;Rabe et al, 1996). Nevertheless, progestogens are still classified as potentially carcinogenic in human by the International Agency for Research on Cancer (IARC) and it was reported that in human liver slices, CPA induced DNA adducts (Baumann et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Because this drug is widely used in clinic, many studies have adressed its carcinogenic potential in human and most of the studies have come to the agreement that the liver cancer risk associated with the use of CPA is low, if it exists (Hinkel et al, 1996;Kasper, 2001;Kattan et al, 1994;Laron and Kauli, 2000;Rabe et al, 1996). Nevertheless, progestogens are still classified as potentially carcinogenic in human by the International Agency for Research on Cancer (IARC) and it was reported that in human liver slices, CPA induced DNA adducts (Baumann et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Formation of cyproterone acetate-DNA adducts in human liver cells was also reported by Bauman et al (1996) who used human liver slices of male and female donors for their studies and found a dose-dependent formation of one main adduct in a concentration range of 0.1-5 mg cyproterone acetate/ml. In comparison to isolated hepatocytes the liver slice system has some advantages in that the structural heterogeneity of the liver is preserved and thus the slices more closely resemble the in vivo situation than hepatocytes (Baumann et al 1996). In general, the good concordance between genotoxic effects found in human and rat cells at the in vitro level in response to cyproterone acetate suggests that the female rat appears to be appropiate for modelling adverse effects related to genotoxicity in the human liver.…”
Section: Genotoxicity Studies In Human Liver Cellsmentioning
confidence: 99%
“…One approach is to compare the effect of a drug in cultured human and animal tissue, providing information about the potential species-specificity of drug-induced adverse effects, otherwise unavailable in the preclinical phase of safety testing. Precisioncut tissue slicing has been a very useful tool in this respect (Smith et al, 1985), and has been increasingly used for interspecies comparisons of toxicity (Fisher et al, 1991(Fisher et al, , 1995Price et al, 1996), metabolism (Steensmae/ al., 1994Connors et al, 1996), liver enzyme induction (Glockner et al, 1995;Heinonen et al, 1996;Lake et al, 1996a), and genotoxicity (Baumann et al, 1996;Beamand et al, 1996;Lake et al, 1996b). Using the same preparative technique in all species, slices are relatively simple to prepare from almost any organ, including important targets of toxicity, such as the liver (Smith et al, 1985), lung (Fisher et al, 1994;Price et al, 1995a,b), and kidney (Ruegg, 1994).…”
Section: European Legislative Mandate (Iain Purchase)mentioning
confidence: 99%